Feeding systems and implant strategies for calf-fed Holstein steers - C.T. Milton; Robert T. Brandt Jr.; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1998)
Two hundred sixty-four Holstein steer calves (308 lb) were used in a 2x3 factorially designed experiment to compare the effect of two feeding systems and three implant strategies on performance and carcass characteristics. Steers were allowed ad libitum access to a conventional, high-grain diet for the entire feeding period or were program-fed a high-grain diet to gain 2.2 lb/d for 109 days and 2.6 lb/d for 92 days and then allowed ad libitum access to feed for the remainder of the feeding period. Steers were fed to a common weight endpoint (1260 lb). Implant strategies were: 1) Synovex® -S on days 1, 109, and 201 (S-S-S); 2) Synovex® -C on day 1, Synovex-S ® on day 109, and Revalor -S on day 201 (C-S-R); and 3) Synovex-C on day 1 and Revalor-S on days 109 and 201 (C-R-R). Over the entire feeding period, steers finished on the ad libitum system consumed 7% (P<.01) more feed daily and gained 7.2% (P<.01) faster than those in the programmed feeding system. Steers in the programmed feeding system required an additional 24 days to achieve similar finished weights and had smaller (P<.05) ribeye areas and less (P<.01) backfat than steers feeding ad libitum throughout. Feed efficiency and total feed consumed were similar between feeding systems. Compared to S-S-S, feed efficiency was improved 4.3% by C-S-R and 6.7% (P<.05) by C-R-R. The C-R-R implant strategy reduced marbling (P<.01) and percentage of USDA Choice carcasses (P=.01) compared with S-S-S or C-S-R. A two-phase, programmed feeding system can result in improved feed efficiency and a compensatory gain response during the latter phase of the feeding period. However, the gain restriction over the first 200 days in this study probably was too severe to allow program-fed steers to finish at a similar weight with a similar number of days on feed those feeding ad libitum. Implanting calf-fed Holstein steers with a low dose of estrogen and then increasing implant potency step-wise optimized performance and carcass quality.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; Holstein; Calf-fed steers; Feeding systems; Implants; Carcasses